Emerging Technologies for the Energy Systems of the Future - Anvari-Moghaddam, Amjad; Mohammadi-ivatloo, Behnam; Mohammadi, Fazel; Vahidinasab, Vahid; Razzaghi, Reza (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Energy systems are transiting from conventional energy systems to modernized and smart energy systems. This Special Issue covers new advances in the emerging technologies for modern energy systems from both technical and management perspectives. In modern energy systems, an integrated and systematic view of different energy systems, from local energy systems and islands to national and multi-national energy hubs, is important. From the customer perspective, a modern energy system is required to have more intelligent appliances and smart customer services. In addition, customers require the provision of more useful information and control options. Another challenge for the energy systems of the future is the increased penetration of renewable energy sources. Hence, new operation and planning tools are required for hosting renewable energy sources as much as possible.